1999
DOI: 10.1074/jbc.274.11.7431
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Go-proteins by Membrane Depolarization Traced by in Situ Photoaffinity Labeling of Gαo-proteins with [α32P]GTP-azidoanilide

Abstract: GTP-binding trimeric proteins have been implicated in signal transduction from receptors in the cell membrane to intracellular effectors and ion channels in a variety of cells (1-5). The mechanism involves signal-induced G-protein activation initiated by an exchange of GDP for GTP on the ␣ subunit of the protein (5-7). Subsequent GTPase activity of the G␣ subunit converts the activated G-proteins into their inactive, GDPbound state (7). Activation of G-proteins has been induced experimentally by stimulation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
52
0

Year Published

2000
2000
2006
2006

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(57 citation statements)
references
References 69 publications
(96 reference statements)
5
52
0
Order By: Relevance
“…Our results were consistent with previous biochemical studies showing a voltage-dependent interaction of VGSC with G o protein in rat brain synaptoneurosomes (15). Indeed, R-DPI 201-106, a drug that blocks depolarization-induced activation of G o protein in this preparation (15), also blocked the depolarization-induced inhibition of Ca 2ϩ channels in cerebellar granule cells.…”
Section: Discussionsupporting
confidence: 82%
See 4 more Smart Citations
“…Our results were consistent with previous biochemical studies showing a voltage-dependent interaction of VGSC with G o protein in rat brain synaptoneurosomes (15). Indeed, R-DPI 201-106, a drug that blocks depolarization-induced activation of G o protein in this preparation (15), also blocked the depolarization-induced inhibition of Ca 2ϩ channels in cerebellar granule cells.…”
Section: Discussionsupporting
confidence: 82%
“…Indeed, R-DPI 201-106, a drug that blocks depolarization-induced activation of G o protein in this preparation (15), also blocked the depolarization-induced inhibition of Ca 2ϩ channels in cerebellar granule cells. Although it is difficult to determine from the present study whether or not G o protein activation occurred during activation or inactivation of VGSCs, studies in synaptoneurosomes suggested that this may happen as long as depolarization lasts (15). We show here that voltage-dependent activation of G o protein through VGSCs resulted in IP 3 formation and intracellular Ca 2ϩ release.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations